Taxonomic revision of two Indo-Pacific species of Valenciennea (Teleostei: Gobiidae) reveals two new species from the Indian Ocean - Zarei, Fatah; Motomura, Hiroyuki; Chakona, Albert (Zootaxa, 2026)
The gobiid genus Valenciennea Bleeker, 1856 comprises 17 bottom-dwelling species distributed on shallow coral reefs throughout the tropical and subtropical Indo-Pacific. Twelve species have Indo-Pacific distributions: within the Indian Ocean, six of these species are only found in the eastern part, while the other six occur in both eastern and western regions. Valenciennea persica is endemic to the northwestern Indian Ocean. Valenciennea puellaris (Tomiyama, 1956), originally described from Japan, and V. strigata (Broussonet, 1782), originally described from French Polynesia and long regarded as widely distributed across the Indo-Pacific, are each shown here to comprise two distinct species. Analysis of mitochondrial COI sequences, detailed re-examination of material from ichthyological collections, and comprehensive colour-pattern comparisons support recognition of the Indian Ocean population of V. puellaris as a new species for science, described herein as V. schlieweni sp. nov. Similarly, the southwestern Indian Ocean population of V. strigata has also been shown to represent a distinct species, herein described as V. zaboae sp. nov. Each of the two new species is readily distinguished from all congeners by a distinctive colour pattern in live specimens, as well as by a combination of meristic characters (second dorsal- and anal-fin rays, scale counts), first dorsal- and caudal-fin morphology, head and body proportions, and residual pigmentation in preserved specimens. Georeferenced photographic data from iNaturalist and GBIF (703 records of V. puellaris, 797 of V. strigata) were also used to characterise colour-pattern variation across the Indo-Pacific.